ANALISIS PENERAPAN MODEL AIDA (ATTENTION, INTEREST, DESIRE, ACTION) PADA IKLAN SUSU ULTRA VERSI SHEILA ON 7 - Christoper Yudha Erlangga; Gogali, Venessa Agusta; Ichsan Widi Utomo (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This research analyzes the application of the AIDA (Attention, Interest, Desire, Action) model in Ultra's latest advertisement featuring Sheila on 7. The methodology used is descriptive qualitative, with a focus on how the elements of the AIDA model are applied to attract attention, arouse interest, create desires, and drive consumer action. Data was obtained through observing the latest Ultra Milk advertisement. The research results showed that the use of Sheila on 7 was successful in attracting attention and arousing interest. This research concludes that the AIDA-based advertising strategy applied in the Ultra advertisement with Sheila on 7 has attractive images and the inspirational message of this advertisement increases its effectiveness in reaching and influencing the audience. Overall, this ad not only promotes dairy products, but also conveys positive values ​​about health and wellness, making it more than just an ad.